Uvajanje trajnostnih in visokostorilnih tehnologij v pridelavo jabolk (University of Maribor Press, 2023)
Introduction of Sustainable and High Performing Technologies in Apple Production. The publication presents author’s contributions in order to introduce sustainable and high-performance technologies in apple production. The main starting points for a comprehensive approach from the beginning of production to the very end of storage are presented. The included topics describe mechanical pruning, mechanical thinning, root pruning, physiological and microbial stability of fruit, apple harvesting, storage of yield in dynamic atmosphere and lastly ‘0,0-MRL’ plant protection.